2022
DOI: 10.1021/acsami.1c25204
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Superassembly of Light-Responsive Mechanism-Switchable Nanomotors with Tunable Mobility and Directionality

Abstract: Mechanism-switchable nanomotors are expected to exhibit high adaptability and wide applicability. Herein, for the first time, we report a flask-shaped carbon@Pt@fatty-acid nanomotor with a light-induced switch between nonionic self-diffusiophoresis and bubble propulsion. This nanomotor is fabricated through superassembly of platinum nanoparticles on the surface of carbon nanobottles, and fatty acids are infused into the cavity of carbon nanobottles to serve as a light-sensitive switch. Such a nanomotor can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…In addition, to reduce the amount of computation, the FEA simulations were performed in a stationary manner, which means that the CNC-Cu motor is supposed to be at a fixed position. However, the simulated results were only applicable in understanding the possible mechanisms of motion during the initial instant (within 100 ns), which resulted in the autonomous movement of the CNC-Cu. ,, Animations S1–S3 record the temperature distribution, fluid velocity distribution, and pressure distribution in a time-dependent manner during 100 ns, respectively. Figure displays the simulated main parameters highly correlated with the mechanism of motion at different time points.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, to reduce the amount of computation, the FEA simulations were performed in a stationary manner, which means that the CNC-Cu motor is supposed to be at a fixed position. However, the simulated results were only applicable in understanding the possible mechanisms of motion during the initial instant (within 100 ns), which resulted in the autonomous movement of the CNC-Cu. ,, Animations S1–S3 record the temperature distribution, fluid velocity distribution, and pressure distribution in a time-dependent manner during 100 ns, respectively. Figure displays the simulated main parameters highly correlated with the mechanism of motion at different time points.…”
Section: Resultsmentioning
confidence: 99%
“…181,182 Recently, Liu et al reported a light-responsive mechanism-switchable nanomotor with tunable directionality. 150 The nanomotor was composed of a carbon nanobottle framework with Pt nanoparticles assembled on the surface. The cavity of the carbon nanobottle was filled with solid fatty acids.…”
Section: Motion Controlmentioning
confidence: 99%
“…Therefore, it is more desired that the motion of MNMs can be regulated using biologically relevant stimuli, such as temperature, pH and redox potentials, which naturally exist in human bodies. 150,151 For example, the oxygen concentration in tumor sites is lower than that in normal tissues due to the rapid proliferation of cancer cells; the pH in tumor sites is mildly acidic (o6.5), while the pH in normal tissues is nearly neutral (E7.5); the tumor cells show a higher concentration of H 2 O 2 compared to normal cells. It is also observed that the pH difference, as well as the redox potential difference, exists between the extracellular and intracellular microenvironments.…”
Section: Speed Regulationmentioning
confidence: 99%
“…The materials with asymmetric nanostructures have attracted tremendous attention in various application fields in recent years. [1][2][3][4][5] A variety of asymmetric architectures have been created, such as bowl-liked, [6][7][8][9][10] bottle-shaped, [11][12][13][14][15] yolkshell, [16][17][18][19][20] and others. [3,[21][22][23][24][25] In addition, the components of materials with asymmetric nanostructures mainly include silica, [26][27][28] carbon, and [29][30][31] metals.…”
Section: Introductionmentioning
confidence: 99%